2010
DOI: 10.2169/internalmedicine.49.3978
|View full text |Cite
|
Sign up to set email alerts
|

Graves' Disease Associated with Infectious Mononucleosis due to Primary Epstein-Barr Virus Infection: Report of 3 Cases

Abstract: Although the etiology of Graves' disease is still not clear, it is generally suggested that environmental factors such as infections contribute to the development of Graves' disease. We report here three cases of Graves' disease which presented simultaneously with infectious mononucleosis due to primary EBV infection. Acute EBV infection might play an important role in the onset of Graves' disease. These three women complained of a sore throat or neck pain, resembling subacute thyroiditis. In the case of thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…It has been shown that viral infection occasionally induces the production of various autoantibodies, but the titer is not sufficient to lead to clinical manifestations [17]. Nagata et al reported three women with primary EBV infection (age, 19-20 years old) who presented with Graves' disease during the acute phase [18]. TRAb levels were high in all three cases, and a family history of Graves' disease developed in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that viral infection occasionally induces the production of various autoantibodies, but the titer is not sufficient to lead to clinical manifestations [17]. Nagata et al reported three women with primary EBV infection (age, 19-20 years old) who presented with Graves' disease during the acute phase [18]. TRAb levels were high in all three cases, and a family history of Graves' disease developed in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of human Herpes viruses in the pathogenesis of autoimmune thyroid diseases is largely unknown and data from one study did not support their association [25]. However, another study indicated that Graves' disease is linked to infectious mononucleosis due to primary Epstein-Barr virus infection in patients [26]. This suggests that both Herpes virus and Influenza A virus can employ similar mechanisms as Epstein-Barr virus to trigger immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some cases reported to have developed Graves’ disease related to IM (Akahori et al 2010 ), and this child needs long-term follow-up.…”
Section: Discussion and Evaluationmentioning
confidence: 99%